INFORMATION SEEKING IN LIBRARY: STUDY OF THE THINGKING OF MICHEL FOUCAULT - Purwnto Putra (Metakom, 2019)
Users actually have their own power over information managed by libraries, to fulfill their own expectations of truth according to the perspective of the libraryitself. The library is seriously using a variety of theories, methods and technology trying to facilitate retrieval. The concept of this retrieval becomes something very important, the logical reason is that no matter how good the value of information possessed by the library becomes not useful to the user if it cannot be accessed or cannot be rediscovered. However, one thing that needs to be underlined from all the innovations carried out, is generally still focused only on technology and technicality, limited only from the point of view of libraries and librarians.Key word: information seeking, information, user, library